Merangsang Literasi Baca Tulis melalui Permainan Kartu Suku Kata: Pendekatan Kreatif untuk Pembelajaran Bahasa Indonesia - Hildayanti, Mellinda Safitri; Wakhyudin, Husni; Mujilah; Prima, Filia (Melati Institute, 2024)
This article discusses the use of syllable card games as a creative approach to improving literacy in Indonesian language learning. The game aims to make the learning process more fun and interactive, so that it can motivate students to be more active in learning to read and write. Through a case study at SDN SAMBIREJO 02, it was found that this method is effective in improving students' literacy skills. The article also describes the steps of implementing the syllable card game as well as its impact on students' language skills.